2016
DOI: 10.1097/j.pain.0000000000000593
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic attenuation of cross-modal sensory augmentation within the chronic pain insula

Abstract: Pain can be elicited through all mammalian sensory pathways yet cross-modal sensory integration, and its relationship to clinical pain, is largely unexplored. Centralized chronic pain conditions such as fibromyalgia are often associated with symptoms of multisensory hypersensitivity. In the present study, female fibromyalgia patients demonstrated cross-modal hypersensitivity to visual and pressure stimuli compared to age- and sex-matched healthy controls. Functional magnetic resonance imaging (fMRI) revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 76 publications
(114 reference statements)
4
91
0
Order By: Relevance
“…Central processing of non-painful sensory signals may be of particular importance in maintaining clinical pain in FM, in agreement with previous work [29; 42; 58]. Consistently, Harte and colleagues very recently showed that fMRI data during a visual task could discriminate FM patients vs. healthy controls with 82% accuracy[29]. The Multisensory pattern shows early sensory cortical processing attenuation, which is consistent with reduced processing of fine sensory/discriminative properties of stimulus[1; 18; 46; 53], accompanied by amplification of sensory integration (in agreement with [29]) and self-referential aspects of the response, including potential threat of harm[17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Central processing of non-painful sensory signals may be of particular importance in maintaining clinical pain in FM, in agreement with previous work [29; 42; 58]. Consistently, Harte and colleagues very recently showed that fMRI data during a visual task could discriminate FM patients vs. healthy controls with 82% accuracy[29]. The Multisensory pattern shows early sensory cortical processing attenuation, which is consistent with reduced processing of fine sensory/discriminative properties of stimulus[1; 18; 46; 53], accompanied by amplification of sensory integration (in agreement with [29]) and self-referential aspects of the response, including potential threat of harm[17].…”
Section: Discussionsupporting
confidence: 92%
“…Central processing of non-painful sensory signals may be of particular importance in maintaining clinical pain in FM, in agreement with previous work [29; 42; 58]. Consistently, Harte and colleagues very recently showed that fMRI data during a visual task could discriminate FM patients vs. healthy controls with 82% accuracy[29].…”
Section: Discussionsupporting
confidence: 88%
“…Here, BOLD responses to a flashing checkerboard (perceived to be unpleasant by many) were able to differentiate patients from controls with 82% accuracy using SVM [22]. Furthermore, in a smaller subset of patients who underwent a crossover pregabalin/placebo treatment, degree of right insula activation by the visual stimulus was positively correlated with responsiveness to pregabalin, and classified drug versus placebo with 82% accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, analyses of pooled fMRI data from studies utilizing different imaging equipment and analysis procedures have produced informative and consistent inferences about brain structure and function in chronic pain disorders [86, 93, 99]. Emerging approaches to imaging analysis, such as support vector machines, may also prove useful in addressing concerns about replication [77, 123, 196]. These statistical approaches typically divide participant data into 2 groups: (1) ‘training’ groups, used to estimate a distributed pattern that serves as a provisional brain marker, and (2) ‘test’ groups, used to evaluate its predictive accuracy.…”
Section: Recommendationsmentioning
confidence: 99%